2020
DOI: 10.1007/s00167-020-05914-9
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched knee implants in Indonesian and Dutch patients: a need for increasing the size

Abstract: Purpose The aim of this study was to evaluate the anthropometric diferences between knees of Indonesian Asians and Dutch Caucasians and the it of nine diferent knee implant systems. Methods A total of 268 anteroposterior (AP) and lateral knee preoperative radiographs from 134 consecutive patients scheduled for total knee arthroplasty at two diferent centres in Jakarta and Leiden were included. Both patient groups were matched according to age and sex and included 67 Asians and 67 Caucasians. We assessed the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Classical off-the-shelf (OTS) TKA can cause implant overhang, malalignment and abnormal kinematics [ 20 , 41 ]. One reason may be the high variability of knee phenotypes between individuals, ethnicities and sex [ 4 , 7 , 13 , 19 , 22 ]. Customised individually made (CIM) TKA have been developed to overcome these problems and improve outcome after TKA [ 5 , 17 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classical off-the-shelf (OTS) TKA can cause implant overhang, malalignment and abnormal kinematics [ 20 , 41 ]. One reason may be the high variability of knee phenotypes between individuals, ethnicities and sex [ 4 , 7 , 13 , 19 , 22 ]. Customised individually made (CIM) TKA have been developed to overcome these problems and improve outcome after TKA [ 5 , 17 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recently available new implant design with narrow femoral components have addressed this problem to some extent in Saudi patients undergoing knee replacement. 17 Our study indicated that the available prostheses that are mostly used in Caucasian patients, with the exception of the recently available anatomical knee prosthesis, may be larger than ideal for Saudi patients. 17 …”
Section: Discussionmentioning
confidence: 82%
“… 17 Our study indicated that the available prostheses that are mostly used in Caucasian patients, with the exception of the recently available anatomical knee prosthesis, may be larger than ideal for Saudi patients. 17 …”
Section: Discussionmentioning
confidence: 82%
“…A recent study compared Asians and Dutch Caucasians in Indonesia. Measurement of radiography found that Caucasians had large AP and ML size in both femur and tibia, The ML/AP ratios of both sides were higher in Asians, suggesting a wider surface in given AP [ 33 ]. Kim et al conducted a systematic review of knee morphology based on 30 studies (9050 knees); the result showed that white people had larger knee sizes with reduced ML/AP ratio [ 9 ].…”
Section: Discussionmentioning
confidence: 99%